Preparation on the basis of Trichoderma asperellum in the system of biological protection of wheat from Fusarium ear scab - Kolombet L V; Sokolov M S; Chuprina V P; Schisler D A; Samuels G J (浙江大学学报. 农业与生命科学版, 2004)
During the last century, as the area of wheat grown under advanced grain husbandry has increased worldwide, so too has the importance of Fusarium ear scab (FES) (synonym, Fusarium head blight) caused by several species of the fungus Fusarium. Yield losses due to FES can total 20%-40% and more depending on climatic conditions. During the last twenty years epidemics of FES in cereals have become chronic all over the world, including the United States and Russia. The most destructive of these were observed in 1982, 1986, 1990-1996 in USA and in the south of Russia in 1982, 1984, 1988, 1992.The harmful effect of FES is manifested not only in reduced grain yields, but also in the contamination of grains and grain products with mycotoxins, such as deoxynivalenol (DON) and its derivatives (3-alfa acetyl-DON, 15-alfa acetyl-DON), T-2 toxin and zearalenone.Standard means to control FES (cultural control methodologies, chemical pesticides, and FES resistant varieties) have little effect or are not practical and rarely reduce the accumulation of mycotoxins in grain. We have developed a new technique to reduce FES using biological preparations. The technique utilizes wheat seed pretreatment with a biofungicide “Mycol” in combination with spraying wheat plants during flowering with a yeast preparation.Technology for production of Mycol on the basis of Trichoderma asperellum strain GJS 03-35(systematics by Samuels) has been developed. This strain shows hyperparasitic activity against a wide spectrum of plant pathogens, including Fusarium graminearum, a causative agent of FES in wheat. Experiments conducted in the United States demonstrated that spraying wheat plants during flowering with the patented yeast Cryptococcus nodaensis OH 182.9 (NRRL Y-30216) reliably reduces FES development.Tests of the Mycol preparation and the yeast OH 182.9 (EOD) have been performed on the spring wheat “Ivolga” in greenhouse conditions (the Moscow region) and on the winter wheat “Kupava” in field trials in the North Caucasian region. An isolate of F. graminearum was used to insure adequate levels of disease development in greenhouse and field experiments. FES disease severity and incidence, as well as mycotoxin accumulation in wheat grains was studied for single or combination treatments with the biological preparations. Mycol (in concentrations 0.1, 0.5, 1.0, 2.0 kg/t of seeds) was used for wheat seed pretreatment. The yeast preparation EOD (2.0×107 cfu/mL) was applied by spraying wheat plants during flowering. Chemical pesticides (Raxyl, TMTD) and a biological preparation Agat-25K were used as alternative control seed treatments.In greenhouse experiments, inoculations of heads with either biological preparation 4 h prior to inoculation with conidia of F. graminearum significantly reduced FES severity. Application with Mycol reduced DON in wheat grains by 6 to 11 fold. EOD alone or, to a lesser extent, in combination was also highly effective in reducing DON content. For treatments consisting of Mycol and EOD, 1000 grain weights were equivalent or higher than for control plants (both infected, and not infected). Wheat seeds obtained from the plants protected by these biological preparations germinated rapidly and possessed high germination rates compared to the FES control.In field trials, Mycol treatments clearly reduced FES symptoms, apparently providing an immunizing effect against FES. Mycol reduced FES severity and enhanced yield of the wheat varieties used. The effect of Mycol used at a minimum test-dose (0.1 kg/t) was not so pronounced. The greatest reduction of FES development was observed at a dose of Mycol of 1.0 kg per 1 t of seeds used in combination with EOD spraying. Experimental results support the contention that the offered technology has good prospects in controlling wheat Fusarium ear scab.